2020
DOI: 10.1130/g47625.1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fracturing in the middle continental crust as evidence for transient switching of principal stress axes associated with the subduction zone earthquake cycle

Abstract: In the Neves area, eastern Alps, fractures that localized shear zones in middle continental crust above the Alpine megathrust are commonly oriented at a high angle to the inferred long-term shortening direction. Fractures show a segmentation geometry and, locally, a discernible offset, indicating movement opposite to the sense of subsequent ductile shear and implying a switch of principal stress axes σ1 and σ3 during fracturing. We propose that this repeated switch, demonstrated by overprinting relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The oldest structures observed in the granite consist of D 1 shear fractures, cataclasites and breccias. Similar brittle structures pre-dating ductile shear zones are reported from several other crystalline units of the Alps (External and Internal Crystalline Massifs: Bertini et al, 1985;Ceccato et al, 2022;Goncalves et al, 2012;Guermani & Pennacchioni, 1998;Menegon & Pennacchioni, 2010;Oliot et al, 2014;Rolland et al, 2009;Wehrens et al, 2016;Tauern Window: Leydier et al, 2019;Mancktelow & Pennacchioni, 2020;Suretta nappe: Goncalves et al, 2016). In many cases these brittle structures were interpreted to have formed in the biotite stability field, at relatively high T (>350°C) and mid-to-lower crustal conditions (Goncalves et al, 2016;Wehrens et al, 2016).…”
Section: Brittle-to-ductile Evolution and Alpine Peak Metamorphic Con...supporting
confidence: 74%
See 1 more Smart Citation
“…The oldest structures observed in the granite consist of D 1 shear fractures, cataclasites and breccias. Similar brittle structures pre-dating ductile shear zones are reported from several other crystalline units of the Alps (External and Internal Crystalline Massifs: Bertini et al, 1985;Ceccato et al, 2022;Goncalves et al, 2012;Guermani & Pennacchioni, 1998;Menegon & Pennacchioni, 2010;Oliot et al, 2014;Rolland et al, 2009;Wehrens et al, 2016;Tauern Window: Leydier et al, 2019;Mancktelow & Pennacchioni, 2020;Suretta nappe: Goncalves et al, 2016). In many cases these brittle structures were interpreted to have formed in the biotite stability field, at relatively high T (>350°C) and mid-to-lower crustal conditions (Goncalves et al, 2016;Wehrens et al, 2016).…”
Section: Brittle-to-ductile Evolution and Alpine Peak Metamorphic Con...supporting
confidence: 74%
“…In many cases these brittle structures were interpreted to have formed in the biotite stability field, at relatively high T (>350°C) and mid‐to‐lower crustal conditions (Goncalves et al., 2016; Wehrens et al., 2016). Accordingly, they have been interpreted to represent either (a) a prograde phase of brittle Alpine deformation (Guermani & Pennacchioni, 1998), or (b) brittle (seismogenic) deformation at mid‐crustal depths at the Alpine peak metamorphic conditions (Leydier et al., 2019; Mancktelow & Pennacchioni, 2020; Wehrens et al., 2016). It is interesting to note that such brittle‐to‐ductile evolution at peak metamorphic conditions has been reported from different crystalline units across the Alps spanning the whole range of “peak metamorphic conditions” recorded for the different case studies, from sub‐greenschist to high‐pressure amphibolite facies (see Ceccato et al., 2022; Figure 10a).…”
Section: Discussionmentioning
confidence: 99%
“…Semibrittle processes are directly relevant to deformation of the crust and upper mantle, and particularly to earthquake nucleation and rupture through the base of the seismogenic zone. Abundant microstructural evidence confirms a mixed mode of frictional and viscous microprocesses (Fusseis & Handy, 2008; Mancktelow & Pennacchioni, 2020; Melosh et al., 2018; Stewart et al., 2000; Wehrens et al., 2016; White & White, 1983; Zulauf, 2001), which are primarily controlled by lithology and environmental conditions of effective pressure and temperature. While confining pressure and temperature are considered relatively stable in the subsurface, the stress state, strain rate, and fluid pressure are expected to vary considerably over the seismic cycle (Ellis & Stöckhert, 2004; Ivins, 1996; Matysiak & Trepmann, 2012; Nüchter & Stöckhert, 2008; Scholz, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Our laboratory and numerical simulation results open up a fundamental LSB versus C‐ band growth issue in ductile shear zones. Field studies have already demonstrated that an interplay between LSB and shear parallel C bands can occur at mid‐ and lower‐crustal levels (Mancktelow & Pennacchioni, 2005, 2020; Segall & Simpson, 1986; Simpson, 1986). The shear zone model in the present study strengthens earlier views that the visco‐plastic rheology accounts for the dynamic and kinematic growth of both LSB and C‐band structures in natural ductile shear zones at relatively high P‐T conditions.…”
Section: Discussionmentioning
confidence: 99%